Health workforce financing in Uganda: challenges and opportunities. (30th September 2020) - Koutsoumpa, M; Odedo, R; Banda, A; Meurs, M; Hinlopen, C; Kramer, K; Bemelmans, M; Omaswa, F; Ojoome, V; Kiguli-Malwadde, E
Abstract: Background: For health systems to operate well and improve people's health by leaving no one behind, they need a fit-for-purpose health workforce. Shortage of health workers leads to reduced access to healthcare, health inequities, and adverse outcomes in the population's health. A key challenge in many low-income countries is mobilising the needed investment for health workforce development. This study evaluated the policy environment of the health workforce in Uganda, analysed its current status, and identified financing mechanisms and management practices that affect the country's health resource envelope. Methods: The study was conducted in 2018/19. It entailed literature review, key informant interviews and stakeholder consultations for validation of the findings. Results: The shortage of health workers is persevering, despite efforts of the Ugandan Government and development partners. The health workforce is not keeping up with the population growth, nor the epidemiologic changes and demographic trends. Paradoxically, there is a large pool of qualified and licensed health professionals, who remain unabsorbed. Notably, even if all of them were absorbed, Uganda would be still far from the international requirements for universal health coverage. The issues are recognized at the policy level, but insufficient funding and poor management are impeding the recruitment and retention of health workers. Domestic resources are insufficient to fund a health system which can offer a minimum healthcare package and most donors are reluctant to contribute to health workers' salaries. Besides, Uganda is lacking a national health insurance scheme, which keeps out-of-pocket spending on health at very high rates. Moreover, increases in external financing have been accompanied by decreases in domestic government financing, despite economic growth. Conclusions: The health sector financing is influenced by a complex political economy, which impedes investments in the health workforce. Key messages: The problems and gaps of the Ugandan human resources for health are persisting due to the insufficient financial allocation and the poor management of the health workforce and existing funds. The shortage of health workers is a global health issue that goes beyond national borders and the health sector. It is an essential requirement for exercising the universal right to health.